« This thin world of ghosts, of outlines, of abstract densities » : l’écriture hantée de Rosamond Lehmann - Jessica Billy-Le Flem (Caliban: French Journal of English Studies)
Scarred by the trauma of the First World War, Rosamond Lehmann’s characters evolve in a spectral world marked by absence and death. For the writer, the ghostly representation of post-war life is both a literary and a metaphysical issue. Caught between an ineffable past and an uncertain future, the present can only be represented through the exploration of an in-between, erasing the boundaries between visible and invisible, present and past, embodied and disembodied. The fictional work, haunted by spectral figures and heterogeneous intertexts, eventually finds resolution by implementing visual strategies and experimenting with photographic techniques.